Błędne reprezentacje a pojęcie funkcji w teleosemantyce. Analiza koncepcji Dretskego i Millikan - Bielecka, Krystyna (Filozofia Nauki, 2014)
The paper analyzes the attempts to account for the nature of misrepresentation in terms of 'teleosemantic' functions as offered by Dretske and Millikan. In two first parts of the paper, Dretske's teleosemantics and the role his account of function plays in his teleosemantics are investigated. In the third part, Dretske's concept of function is compared to the one defended by Millikan (although her theory of representation is not taken into consideration here). On the one hand, Millikan's theory is similar to Dretske's but on the other hand, it is much better worked out and, as a consequence, it is less controversial than Dretske's. In the fourth part, my analysis is summarized. Finally, the critical conclusions concerning Dretske's teleosemantics as well as the use of the concept of function in naturalizing representation are presented.